Variant in PNPLA3 is associated with alcoholic liver disease - Tian, Chao; Stokowski, Renee P; Kershenobich, David; Ballinger, Dennis G; Hinds, David A (Nature genetics, 2010)
David Hinds and colleagues report that a non-synonymous variant in PNPLA3 is associated with alcoholic liver disease and liver cirrhosis. This result follows previously reported associations of this variant with nonalcoholic fatty liver disease. Two genome-wide association studies (GWAS) have described associations of variants in PNPLA3 with nonalcoholic fatty liver and plasma liver enzyme levels. We investigated the contributions of these variants to liver disease in Mestizo subjects with a history of alcohol dependence. We found that rs738409 in PNPLA3 is strongly associated with alcoholic liver disease and clinically evident alcoholic cirrhosis (unadjusted OR= 2.25, P =1.7 × 10 −10 ; ancestry-adjusted OR=1.79, P =1.9 × 10 −5 ).